Potential Role of Yeast Strains Isolated from Grapes in the Production of Taurasi DOCG - Aponte, Maria; Blaiotta, Giuseppe (Frontiers in Microbiology, 2016)
Twelve samples of Aglianico grapes, collected in different locations of the Taurasi DOCG (Appellation of Controlled and Guaranteed Origin) production area were naturally fermented in sterile containers at room temperature. A total of 70 yeast cultures were isolated from countable WL agar plates: 52 in the middle of the fermentation and 18 at the end. On the basis of ITS-RFLP analysis and ITS sequencing, all cultures collected at the end of fermentations were identified as Saccharomyces (S.) cerevisiae; while, the 52 isolates, collected after one week, could be referred to the following species: Metschnikowia (M.) pulcherrima; Starmerella (Star.) bacillaris; Pichia (P.) kudriavzevii; Lachancea (L.) thermotolerans; Hanseniaspora (H.) uvarum; Pseudozyma (Pseud.) aphidis; S. cerevisiae. By means of Interdelta analysis, 18 different biotypes of S. cerevisiae were retrieved. All strains were characterized for ethanol production, SO2 resistance, H2S development, β-glucosidasic, esterasic and antagonistic activities. Fermentation abilities of selected strains were evaluated in micro-fermentations on Aglianico must. Within non-Saccharomyces species, some cultures showed features of technological interest. Antagonistic activity was expressed by some strains of M. pulcherrima, L. thermotolerans, P. kudriavzevii and S. cerevisiae. Strains of M. pulcherrima showed the highest β-glucosidase activity and proved to be able to produce high concentrations of succinic acid. L. thermotolerans produced both succinic and lactic acids. The lowest amount of acetic acid was produced by M. pulcherrima and L. thermotolerans; while the highest content was recorded for H. uvarum. The strain of Star. bacillaris produced the highest amount of glycerol and was able to metabolize all fructose and malic acid. Strains of M. pulcherrima and H. uvarum showed a low fermentation power (about 4%), while, L. thermotolerans, Star. bacillaris and P. kudriavzevii of about 10%. Significant differences were even detected for S. cerevisiae biotypes with respect to H2S production, antagonistic activity and β-glucosidase activity as well as for the production of acetic acid, glycerol and ethanol in micro-vinification experiments.